ANALISIS KEBISINGAN PADA RUANG BACA BADAN PERPUSTAKAAN DI SMP IT AL HIJRAH 2 - Anggi Sofiana Nasution; Budi; Tika Kesuma Wardani; Muhammad Ibnu; Yudha Nur Diamsyah; Maulana Harin Hanafi (Journal of Community Devation, 2024)
The reading room is one of the important facilities in schools which is used to support the teachingand learning process. A calm and conducive reading room atmosphere is very important tosupport students' concentration and focus in reading and studying. This research aims to analyzethe noise level in the Library Board reading room at SMP IT Al Hijrah 2. Data was collectedthrough direct observation, interviews with librarians and students, as well as documentationanalysis. The results of the research show that the noise level in the Library Board reading roomat SMP IT Al Hijrah 2 still exceeds the comfort threshold. This is caused by several factors, suchas students talking and playing, noise from outside the room, and lack of soundproofing in theroom. Based on the research results, it is recommended to make several efforts to reduce noiselevels in the reading room, such as increasing student discipline, installing soundproofing in theroom, and providing a more conducive reading room.Keywords: Noise, Reading Room, Library.